RESEARCH OF INFORMATION SYSTEMS DESIGN SOFTWARE - Тursynbayev А.З.; Balganova М.С.; Khojaniyazova Г.М.; Shaukhan С.Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The main goal is to maximize automation of system design and analysis stages in order to create formal and nonlinear models of the system. Many modern CASE tools support structural and object-oriented methodologies for analyzing and designing information systems. The software is intended for solving specific user tasks and mainly for organizing the computing process of an information system. The application package is a powerful tool for automating user-defined tasks. It completely frees the user from the need to know how the functions and procedures of information processing are performed on the computer. CASE technologies are usually used when creating complex information systems that require collective project implementation. The absolute advantage of CASE technology is that documents are always responsible for the current state of work. Because any changes in the project are automatically displayed in the database.